Influence of Carbon Source and Culture Condition on Arachidonic Acid Production by Candida Krusei in Submerged Culture - Noraziah, Abu Yazid; Nurul Izyani, A.M. (2012)

(untitled)
The growing interest in the application of arachidonic acid (AA) in pharmaceutical and dietary requirements has obtained much attention on production of AA by microorganism. The influence of carbon sources and culture condition on arachidonic acid production was investigated in cultures of Candida krusei using shake flasks. The optimum culture condition for high yield of AA was determined by varying the pH (in range of 5 to 9) and agitation speed (in range of 50 to 250 rpm). The carbon sources that were used are sucrose, starch and the mixture of sucrose and starch. The highest dry biomass concentration (0.1473 g/ml) was obtained under culture condition at pH 7 and 250 rpm agitation rate by using sucrose as a carbon source. While, the highest yield of AA (5.0916 g/ml) was produced at pH 7 and 150 rpm agitation rate by using sucrose as carbon source.